KEMAMPUAN PENJUMLAHAN ANAK TUNAGRAHITA RINGAN MELALUI MEDIA KARTU REMI - Eza - Yusdial (Universitas Negeri Padang, 2014)
The research was motivated by the problems of children mental retardation (x) which is difficult to solve the sum. The child has difficulty in working on the sum of numbers 1 to 10, Researchers wanted to be the sum capacity can be increased by using the playing cards media. The hypothesis in this study, can improve the ability of the media playing cards summation for mental reterdation. This research uses experimental approach in the form of Single Subject Research (SSR) with A-B design. As the subject of this study is Mental Reterdation child (x) class D.VI/C in special school Perwari Padang. It is shown that the ability of the sum of numbers from 1 to 10 for mild mental retardation children increased. At the baseline condition ( A ) the child is able to resolve the matter with the acquisition sum percentage of correct answers between 20 % - 40 %, after a given intervention ( B ) by using the media playing cards percentage of correct answers increased to 40 % - 100 % . Thus, the hypothesis put forward previously acceptable . This means that the media playing cards can increase the ability of the sum of the child class mild mental retardation D.VI / C in special school Perwari Padang .